Design styles features for youth cafes (Journal of the College of Basic Education, 2022)
When we talk about someone's style, we mean their personal taste and unique way of doing things.As for interior design, there are specific designs associated with certain countries-or eras, meaning that the way the people of that country-era do things enables anyone to create dozens of designs, and styles that I will address, for example, but not limited to.And due to the diversity of models used at the present time and their ramifications that did not take into account the appropriateness of the developments that took place, through this it becomes clear to us that the idea of ​​the types of design models was not defined in an extensive and specific way. Thus, the research objective is defined as follows: